Analysis of Textbooks for Preparation of Linguists in French Universities - Halus, Oleksandr; Abramov, Oleksandr (Pedagogical Discourse, 2015)
The article describes the content and the structure of modern textbooks and manuals for training linguists in universities in France. The methods of work with the textbooks and manuals as for learning English and French have been analyzed. The attention is focused on the processes of teaching and assessment the knowledge of students. It is concluded that the studied methods are designed for four levels of proficiency: A1, A2, B1, B2. Each level of study includes: the book for students with the CD, booklet with tasks for the students, the teacherʼs book, video (DVD or VHS) and corresponds the Common European Framework of Reference for Languages: learning, teaching, assessment. Four modern English textbooks New English File, New Total English, Speаkout, Upstream have been analyzed. These textbooks are the complex training course which consists of the main textbook, workbook, teacher’s book and audio and video CDs. The training course gives chance to improve all skills: to listen and understand foreign language by ear, to read, write and speak English. The textbooks are normally divided into lessons-units and every lesson contains sections: oral speech (Speaking) – questions for discussion, exercises for oral speech development; language perception by ear (Listening) – audio CDs and tasks them; reading – some texts, which form the basis for development of speaking and learning new words; writing – tasks for training written language; grammar – the block, which explains any aspect of grammar with simple words, as well as the exercises for training theory in practice; vocabulary – selection of words and word-expressions, and also the exercises to practice their usage; pronunciation – exercises with audio CDs for training short pronunciation of sounds of the English language. The analysis of methods of teaching French language of the French publishing houses Didier, Hachette, CLE international has been given. Almost every year new textbooks on French language appear, with remedial action and the search of new, more colorful presentation of the methods of teaching comparing to the competitors. During the recent years the publishing houses offer electronic textbooks as well.